The Impact Analysis of E-Commerce Usage on Behavior Changes of Shopee Customers in Indonesia - Silvia Ekasari; Yusi Faizathul Octavia; Y. R. Satato; Ratnawita; Putri Ekaresty Haes (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study was to determine the impact of e-commerce on changes in habits and consumptive behavior among online buyers. The research method used is qualitative research, with data collection techniques through in-depth interviews with ten informants consisting of students and employees who have shopped online at least once a month. The results of the study show that the presence of various e-commerce platforms in Indonesia influences the changing patterns of people's shopping in this digital era. Consumer trust in e-commerce exists because the hopes and expectations that exist in the community as online buyers can be realized. The existence of various e-commerce sites in Indonesia has an influence on people's shopping habits. In addition, the influence of product advertisements, flash sales, free shipping, and discounts makes people, as consumers, continuously want to shop online, resulting in a consumptive lifestyle. In line with Baudrillard's consumptive theory, consumers in e-commerce shop no longer because of use value or exchange value but because there is a sign value attached to the product. So that people no longer buy goods to fulfill their daily needs but to fulfill their desires and to improve their image, lifestyle, and social status in society.